Procedimentos contábeis gerenciais e elaboração de estratégias: um estudo em empresas comerciais na Região do Cariri Ocidental Paraibano - Melo, Wilton Alexandre de (2019)
The objective of this study was to analyze the relationship between the use of managerial procedures and the process of strategy development in the smaller companies that are part of the Cariri Western Paraíba region. With support on the principles of Resource Based on Vision Theory (VBR), we adopted a perspective of the internal environment, where are produced and made available the informations to the managers. This is a descriptive survey, developed by means of a survey of information about the data that were released in five parts, the first and second part treated of the description by respondents and companies, a third and a fourth , the use and importance of management artifacts, and the fifth approached strategic procedures. It was applied to a sample of 55 companies from the supermarket sector in the region of Cariri Western Paraíba, chosen by accessibility. The analyzes were carried out using descriptive statistics as a Spearman correlation, in order to verify the difference between: profile of the participants, profile of the companies, application of managerial procedures and process of elaboration of strategies. As a result, the manageable accounting procedures more used are operational control (52.1%), followed by costs (33.4%) and the less used are accounting statements (38.9%) and other artifacts (46 9%). The importance of these procedures we found that - Control rules ensure that data are controlled, costs, accounting controls, and other artifacts – are considered important or very important to the respondents, indicating a divergence between a use and a perception of importance. The elaboration of process aspects of strategy got 65,4% of agreement with the 32 analyzed variables, beeing that the creativity and intuition were considered by the sample how basilars elements on the strategey formation, obtaining a higher average on the presented evaluation (47,3%). In what concerns to the correlations, the participants and companies profile showed up practically indifferent to the use of acountting management tools and to the process of strategic elaboration, in this presenting some correlations with the schooling and time of action of the participants. Finally, in relations between the use of accounting procedures and the process of strategic elaboration was mainly that the control of cash, balance sheet and the break-even point,were presented greater recurrence and on the other artifacts there was a more egalitarian distribution between analyzed procedures. Thus, the results have evidenced the reaserched understood the importance of managerial processes in the strategic process, but they still do not use them fully, which may compromise a search for a competitive differential.